2021
DOI: 10.5271/sjweh.4006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating effectiveness of an integrated return-to-work and vocational rehabilitation program on work disability duration in the construction sector

Abstract: This study examines the effectiveness of an integrated return-to-work (RTW) and vocational rehabilitation (VR) program on cumulative disability days paid to injured workers in the construction sector in Ontario, Canada. The findings suggest that the program reduced cumulative disability days paid to all claims but particularly long-duration claims referred to RTW specialists and short-duration claims referred to VR specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…For example, Finnish researchers showed that the use of part-time sick leave during the first three months of sickness absence resulted in earlier return-to-work among persons with mental disorders and musculoskeletal diseases ( 40 ). Likewise, the introduction of a work reintegration programme in the construction industry in Ontario, Canada, was associated with less disability days after a work-related injury ( 41 ).…”
Section: Emerging Evidence From Interventionsmentioning
confidence: 99%
“…For example, Finnish researchers showed that the use of part-time sick leave during the first three months of sickness absence resulted in earlier return-to-work among persons with mental disorders and musculoskeletal diseases ( 40 ). Likewise, the introduction of a work reintegration programme in the construction industry in Ontario, Canada, was associated with less disability days after a work-related injury ( 41 ).…”
Section: Emerging Evidence From Interventionsmentioning
confidence: 99%
“…Preventing and mitigating burnout is crucial for maintaining a healthy and productive healthcare workforce. Strategies for preventing burnout among healthcare workers can include job redesign, social support, stress management, and individual-level interventions such as mindfulness training and resilience building (20,21).…”
Section: Impact For Health Care Practitioners In the Capacity Of Case...mentioning
confidence: 99%